2013
DOI: 10.1123/jsr.22.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play in Elite Rugby Union: Application of Global Positioning System Technology in Return-to-Running Programs

Abstract: An analysis of the position-specific physical demands measured by GPS provides key information regarding the level and volume of loads sustained by a player in a game environment. Using this information, sports-medicine practitioners can develop rehabilitation and return-to-running protocols specific to the player position to optimize safe return to play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 16 publications
0
25
2
4
Order By: Relevance
“…This result is in contrast with previous research, [3,[10][11][12] which has reported backs covering a higher amount of relative distance than forwards. Notably, these previous studies have also reported higher relative speeds for backs than the present study, while the relative distance covered by forwards was comparable.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This result is in contrast with previous research, [3,[10][11][12] which has reported backs covering a higher amount of relative distance than forwards. Notably, these previous studies have also reported higher relative speeds for backs than the present study, while the relative distance covered by forwards was comparable.…”
Section: Discussioncontrasting
confidence: 56%
“…[9] To date, only four studies have been published describing the movement characteristics of elite professional rugby union players. [3,[10][11][12] The first two of these, Cunniffe et al [3] and Coughlan et al, [10] used similar methodology: tracking a single forward and a single back during an international rugby union match. The results were similar: players covered >6 500 m in both studies and the backs performed a greater number of high-intensity runs and reached greater maximal speeds than the forwards did.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent technological innovations have made GPS athlete-tracking a convenient and popular method to quantify movement patterns and physical demands in sport (1,2,15,26). Global positioning system technology has been used to quantify the physiological demands of sports such as rugby league (4,5,23,39), rugby union (27,43,48), and Australian Rules (28,31). In a study on the validity and reliability of GPS in team sport movement demands, Johnston et al (29) reported that GPS seems to be a practically superior athlete-monitoring system in comparison with other methods (e.g., time-motion analysis, hand notation techniques, video-based systems).…”
Section: Introductionmentioning
confidence: 99%